2013
DOI: 10.1111/nyas.12098
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes in East Asians: similarities and differences with populations in Europe and the United States

Abstract: There is an epidemic of diabetes in Asia. Type 2 diabetes develops in East Asian patients at a lower mean body mass index (BMI) compared with those of European descent. At any given BMI, East Asians have a greater amount of body fat and a tendency to visceral adiposity. In Asian patients, diabetes develops at a younger age and is characterized by early β cell dysfunction in the setting of insulin resistance, with many requiring early insulin treatment. The increasing proportion of young-onset and childhood typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
616
4
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 675 publications
(646 citation statements)
references
References 221 publications
21
616
4
5
Order By: Relevance
“…This finding concurs with a report that East Asians tend to have a higher prevalence of diabetes at a lower BMI compared to Americans and Europeans [29]. Other studies have found similar higher prevalence rates of diabetes at lower BMIs among Asians [30].…”
Section: Discussionsupporting
confidence: 79%
“…This finding concurs with a report that East Asians tend to have a higher prevalence of diabetes at a lower BMI compared to Americans and Europeans [29]. Other studies have found similar higher prevalence rates of diabetes at lower BMIs among Asians [30].…”
Section: Discussionsupporting
confidence: 79%
“…Scopinaro et al (40) have done BpD for the patients with the same range of BMI and used the same definition of remission of T2DM. Remission rate was 67%, much lower than that reported by Lee et al This difference may be partially explained by the fact that Asian population has a higher amount of body and visceral fat at any given BMI as compared to Europeans (41). However, the findings of this study should be confirmed by other RCTs in different populations.…”
Section: Sg Versus Gastric Bypasscontrasting
confidence: 55%
“…Similar risk factors for T2DM have been identified in Europids and in Asian populations (5,6,54). Many of these risk factors are closely linked to economic development and the increasing urbanization seen across much of Asia and the Pacific.…”
Section: Risk Factors For Diabetes In Asians and Pacific Islandersmentioning
confidence: 82%
“…Studies that have examined the association between adiposity and diabetes in multiethnic cohorts noted that Asians develop diabetes at a considerably lower BMI compared with Europids (54,68). This is ascribed to visceral adiposity in Asian populations (69).…”
Section: Risk Factors For Diabetes In Asians and Pacific Islandersmentioning
confidence: 99%